Обет молчания: [роман] / Марселла Бернстайн - Бернстайн Марселла (Азбука-классика, 2008)
Экземпляры: Аб (20140324) / Инвентарный номер: 100916 / Цена: 100.00 / Авт.знак: Б 51 / ГРНТИ: 17.82 / ББК: 84(4Вел)